Altitude illness - Barry, P; Pollard, A (BMJ Publishing Group, 2003)
Summary points: Altitude related illness is rare at altitudes below 2500 metres but is common in travellers to 3500 metres or more. The occurrence is increased by a rapid gain in altitude and reduced by a slow ascent, allowing time for acclimatisation. For most travellers, altitude related illness is an unpleasant but self limiting and benign syndrome, consisting chiefly of headache, anorexia, and nausea. More severe forms of illness including cerebral or pulmonary oedema may occur and may be fatal, particularly if not recognised. The treatment of altitude related illness is to stop further ascent and, if symptoms are severe or getting worse, to descend. Oxygen, drugs, and other treatments for altitude illness should be viewed as adjuncts to aid descent.